Analisis Dan Evaluasi Terhadap Pandangan Thomas Aquinas Tentang Gambar Allah - Adi Putra (Manna Rafflesia, 2020)
This study discusses the analysis and evaluation of Thomas Aquinas's view of the "image of God". Through qualitative research with a literature review approach, the following conclusions are obtained Aquinas's view of God's image is very unbiblical. Because it is more inclined to the philosophy of Plato and Aristotle. This is a characteristic of scholastic group theology. Because scholastic theologians tend to place ratios more dominant in theology than the Bible. Furthermore, the image of God carried by humans is not only in the ratio but in the totality of human existence in the earth as God's representative. The image of God in humans experiences severe damage after the fall of man in sin. The ratio is no better than the body. In other words, all parts of human beings, whether spirit, ratio, morals, body, when created in a noble or very good state. This rejects Aquinas's view that there are inferior forces. Finally, through this research, we want to stress that the image of the true God is in Christ. This has the effect that it is only through Christ that the image of God that has been badly damaged can be repaired.